Konseling Agama Pada Siswa Pecandu Narkoba - Musa Masing (PEADA': Jurnal Pendidikan Kristen, 2020)
The purpose of giving counseling for drug addicts students is to correct mistakes that are the new direction and purpose of life in God. Direction of life to God who will be equipped to a better future. In this study using qualitative research with case study techniques. The subjects in this study consisted of 2 students, junior high school students in Samarinda City who were addicted to drugs but were undergoing rehabilitation at the Tanah Merah Samarinda Rehabilitation Center and one person as a mental mentor of religion. This research focuses on Religious Counseling on addicted students. The purpose of this research is to find out the type of religious counseling used for drug addicts students who are undergoing rehabilitation at the BNN Tanah Merah Rehabilitation. The results showed that there were 6 Religious Counseling conducted at the Tanah Merah Samarinda Rehabilitation Center for DT and KS Clients, namely 6 Supportive-Counseling, Confrontational-Counseling, Educative-Counseling, Spiritual-Counseling, Group-Counseling, Preventive-Counseling. Tujuan pemberian konseling bagi siswa pecandu narkoba adalah memperbaiki kesalahan yang menjadi arah dan tujuan hidup baru di dalam Tuhan. Pengarahan hidup kepada Tuhan yang akan menjadi bekal menuju masa depan yang lebih baik. Dalam penelitian ini menggunakan penelitian Kualitatif dengan Teknik studi kasus. Subjek dalam penelitian ini terdiri dari 2 yaitu Siswa Sekolah Menengah Pertama (SMP) di Kota Samarinda yang menjadi Pecandu narkoba tetapi sedang menjalani rehabilitasi di Balai Rehabilitasi BNN Tanah Merah Samarinda dan satu orang sebagai Pembina mental Agama. Penelitian ini menfokuskan pada Konseling Agama pada siswa pecandu. Tujuan Penelitiannya adalah untuk mengetahui jenis konseling agama yang digunakan bagi siswa pecandu narkoba yang sedang menjalani rehabilitasi di Balai Rehabilitasi BNN Tanah Merah Samarinda.  Hasil penelitian menunjukkan bahwa Konseling Agama yang dilakukan di Balai Rehabilitasi BNN Tanah Merah Samarinda kepada Klien DT dan KS ada 6 yaitu Supportive-Konseling, Confrontational-Konseling, Educative-Konseling, Spiritual-Konseling, Group-Konseling, Preventive-Konseling.